Photo-curable pressure-sensitive composition

The photocurable releasable pressing composition, comprising specific components and blending ratios, addresses the challenge of maintaining stable releasability and preventing ink transfer in information carrying sheets, ensuring adequate adhesive strength and confidentiality.

JP2025043414APending Publication Date: 2025-04-01AICA KOGYO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023150650
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing photocurable adhesives for information carrying sheets face challenges in maintaining stable releasability without a sudden increase in peeling force over time, while also preventing ink transfer during inkjet printing.

Method used

A photocurable releasable pressing composition comprising an acrylic block copolymer, ethylene oxide-modified bisphenol A diacrylate, a multifunctional (meth)acrylate derived from trimethylolpropane and/or pentaerythritol, and a photopolymerization initiator, with specific blending ratios to ensure adequate adhesive strength and stable releasability.

Benefits of technology

The composition achieves sufficient adhesive strength to maintain confidentiality of the information surface while ensuring stable releasability without a sudden rise in peeling force over time, and prevents ink transfer during inkjet printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043414000001
    Figure 2025043414000001
  • Figure 2025043414000002
    Figure 2025043414000002
  • Figure 2025043414000003
    Figure 2025043414000003
Patent Text Reader

Abstract

To provide a pressure-sensitive composition which, after bonding through photocuring, can retain the information surface in a concealed state while having sufficient adhesion, does not exhibit a sudden increase in peel strength over time, and can maintain re-peelability under low peel strength.SOLUTION: A photo-curable re-peelable pressure-sensitive composition comprises an acrylic block copolymer, ethylene oxide-modified bisphenol A diacrylate, multifunctional (meth)acrylate, and a photopolymerization initiator, wherein the multifunctional (meth)acrylate is derived from trimethylolpropane and / or pentaerythritol, and is contained in a proportion of 15-55 wt.% relative to the total amount of solids.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-bonding resin composition which is cured by exposure to light such as ultraviolet light and has good removability. [Background technology]

[0002] Traditionally, envelopes have been used to send information while keeping it concealed, but now V- or Z-shaped postcards are used, on which information can be written and glued on the inside so that the information can be mailed while maintaining its concealment; these are generally referred to as information carrying sheets.

[0003] The adhesive used in this information-carrying sheet must be easy to remove but difficult to reattach, and initially water-based latex or emulsion was used, with the applicant also having previously invented a composition consisting of vinyl acetate emulsion, plasticizer, and fatty acid calcium (Patent Document 1). However, these water-based adhesives had many problems, such as requiring a long time to dry after application and the base paper being prone to expansion, contraction, and warping due to moisture absorption.

[0004] Therefore, as an adhesive that can deal with such problems, ultraviolet-curing adhesives that can be cured in a short time have come to be used, and in the past, the applicant has also invented a composition consisting of bisphenol A ethylene oxide modified diacrylate, di(meth)acrylate with an alkylene oxide skeleton, a non-functional acrylic polymer, and a photopolymerization initiator (Patent Document 2). This composition has excellent properties such as being less likely to warp even when applied to a substrate and left to stand after curing, and being less likely to cause problems in the lamination process. However, if left to stand for a long time after lamination, the peeling force may increase over time, making it difficult to re-peel. In addition, in recent years, on-demand printing has become mainstream and inkjet printing has increased, and there has been a problem of ink transferring to the adhesive surface during re-peel. Therefore, there has been a demand for a photocurable pressure-sensitive adhesive composition that has sufficient adhesive force to keep the information surface secret after lamination, does not rapidly increase in peeling force over time, can ensure stable re-peelability, and can maintain low adhesion so that ink does not transfer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5008934 [Patent Document 2] Patent Publication No. 2021-075614 Summary of the Invention [Problem to be solved by the invention]

[0006] The object of the present invention is to provide a pressure-sensitive adhesive composition which has sufficient adhesive strength after photocuring and lamination, does not show a sudden increase in peel strength over time, and can maintain stable removability with a low peel strength. [Means for solving the problem]

[0007] In order to achieve the above object, the invention of claim 1 provides a photocurable removable pressure-sensitive composition comprising an acrylic block copolymer (A), an ethylene oxide-modified bisphenol A diacrylate (B), a polyfunctional (meth)acrylate (C), and a photopolymerization initiator (D), wherein (C) is derived from trimethylolpropane and / or pentaerythritol, and the blending amount of (C) is 15 to 55 weight % based on the total solid content.

[0008] The invention of claim 2 provides the photocurable removable pressure-sensitive adhesive composition according to claim 1, characterized in that (A) is a triblock copolymer elastomer of methyl methacrylate and butyl acrylate.

[0009] The invention of claim 3 provides the photocurable removable pressure-sensitive adhesive composition according to claim 1, further comprising a reactive diluent (E).

[0010] The invention according to claim 4 provides a pressure-sensitive adhesive paper having a cured layer of the photocurable removable pressure-sensitive adhesive composition according to any one of claims 1 to 3. Effect of the Invention

[0011] The composition of the present invention has sufficient adhesive strength to keep the information surface concealed after photocuring and lamination, while the peel strength does not increase rapidly over time and can maintain stable removability with a low peel strength, making it useful as a pressure-bonding composition for information-bearing sheets, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The photocurable removable pressure-sensitive adhesive composition of the present invention is composed of an acrylic block copolymer (A), an ethylene oxide-modified bisphenol A diacrylate (B), a multifunctional (meth)acrylate (C), and a photopolymerization initiator (D). In this specification, the term "(meth)acrylate" includes both acrylate and methacrylate.

[0013] The acrylic block copolymer (A) used in the present invention is a plasticizer-like component that is not involved in the curing reaction, and plays a role in reducing warping by stress relaxation, enabling peeling with an appropriate initial peeling force and without leaving any adhesive residue. "Acrylic" means that it contains at least one structural unit derived from a monomer selected from the group consisting of (meth)acrylic acid, fumaric acid, maleic acid and their esters, and (meth)acrylamide and its derivatives, and among these, copolymers consisting of (meth)acrylic acid and its esters are preferred.

[0014] The structure of (A) may be a linear block copolymer, a branched (star) block copolymer, etc., and from the viewpoint of cost, a linear block copolymer is preferred. Among linear block copolymers, diblock copolymers (AB) and triblock copolymers (ABA) composed of two types of monomers (A and B) are more preferred from the viewpoints of ease of handling during processing, physical properties of the composition, and cost.

[0015] As the monomer constituting the (A), methyl methacrylate (hereinafter referred to as MMA) is preferred because the strength and transparency of the cured resin are good and it is easily and inexpensively available. Furthermore, n-butyl acrylate (hereinafter referred to as BA) is preferred because the cured resin has excellent flexibility and good adhesiveness. Examples of block copolymers composed of MMA and BA include a triblock structure (PMMA-PBA-PMMA) composed of a hard segment made of P(poly)MMA and a soft segment made of P(poly)BA, with both ends of the soft segment sandwiched between hard segments. This structure has the characteristics of combining the transparency and weather resistance of PMMA with the flexibility and adhesiveness of PBA.

[0016] When (A) is a triblock copolymer of PMMA-PBA-PMMA, the copolymerization ratio of MMA is preferably 10-50%, more preferably 15-45%, by weight so as to obtain an appropriate balance between adhesive strength and removability. By making the copolymerization ratio of MMA 10% or more, the adhesive strength becomes appropriate, and adhesive residue is unlikely to be left when peeled off, and sufficient removability can be ensured, while by making it 50% or less, the hardness does not become too high and sufficient adhesion can be ensured.

[0017] When the (A) is a triblock copolymer of PMMA-PBA-PMMA, two or more copolymers with different MMA ratios may be used in combination. In this case, the MMA ratio is the guide for the blending ratio, as in the case of using one copolymer alone, and the sum of the values ​​obtained by multiplying the MMA ratio of each of the different copolymers by its content ratio is preferably 10 to 50% by weight (for example, if the blending amount of 50% MMA ratio is 40% and the blending amount of 30% MMA ratio is 60%, the blending amount is 50% by weight x 0.4 + 30% by weight x 0.6 = 38% by weight).

[0018] The weight molecular weight (hereinafter referred to as Mw) of (A) is preferably 30,000 to 200,000, more preferably 50,000 to 150,000. By making it 30,000 or more, sufficient initial peel strength can be ensured, and by making it 200,000 or less, sufficient solubility in the monomer component and viscosity suitable for workability can be ensured. Note that Mw was measured and calculated by gel permeation chromatography using a column using a styrene-divinylbenzene-based packing material and a tetrahydrofuran eluent as the molecular weight in terms of standard polystyrene.

[0019] The amount of (A) based on the total solid content is preferably 1.0 to 10% by weight, more preferably 2.0 to 8.0% by weight, and particularly preferably 3.0 to 6.0% by weight. By making it 1.0% by weight or more, the initial peel strength can be sufficiently ensured, and by making it 10% by weight or less, the viscosity can be easily adjusted to a level suitable for coating.

[0020] The ethylene oxide modified bisphenol A diacrylate (B) used in the present invention is blended for the purpose of improving the curing property and securing the initial peeling force. Since it is modified with ethylene oxide (hereinafter referred to as EO), it can form a cured film with low viscosity and flexibility. The total number of EO modifications added per molecule is preferably 20 or less, more preferably 15 or less, and particularly preferably 10 or less.

[0021] The amount of (B) based on the total solid content is preferably 15 to 55% by weight, more preferably 20 to 52% by weight, and particularly preferably 30 to 50% by weight. By making it 15% by weight or more, sufficient initial adhesion can be ensured, and by making it 55% by weight or less, an increase in peel strength over time can be suppressed.

[0022] The polyfunctional (meth)acrylate (C) used in the present invention has a skeleton derived from trimethylolpropane and / or pentaerythritol, and is blended for the purpose of improving curability and suppressing an increase in peel strength over time and excessive curing progress. Since the distance between the (meth)acryloyl groups, which are polymerizable functional groups, is short, dense bonding points are formed and fixed after the curing reaction, which is thought to suppress an increase in peel strength over time.

[0023] The (meth)acrylate having a skeleton derived from trimethylolpropane means an ester of trimethylolpropane (including ditrimethylolpropane) and (meth)acrylic acid, and also includes compounds modified with an alkyleneoxy group. For example, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and ethylene oxide modified products and propylene oxide modified products thereof can be mentioned, and they can be used alone or in combination of two or more kinds. Among these, trifunctional or higher is preferable, and trimethylolpropane triacrylate (hereinafter referred to as TMPTA) and ditrimethylolpropane tetraacrylate (hereinafter referred to as DTMPT4A) are preferable because of their relatively high glass transition temperature.

[0024] The (meth)acrylate (c2) having a skeleton derived from pentaerythritol means an ester of pentaerythritol (including dipentaerythritol) and (meth)acrylic acid, and also includes compounds modified with an alkyleneoxy group. For example, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ethylene oxide modified products and propylene oxide modified products thereof can be mentioned, and can be used alone or in combination of two or more kinds. Among these, trifunctional or higher functional ones are preferred, and pentaerythritol triacrylate (hereinafter referred to as PET3A) and pentaerythritol tetraacrylate (hereinafter referred to as PET4A) are preferred because of their relatively high glass transition temperature.

[0025] The amount of the (C) based on the total solid content is preferably 15 to 55% by weight, more preferably 20 to 52% by weight, and particularly preferably 25 to 50% by weight. By making it 15% by weight or more, an increase in peel strength over time can be sufficiently suppressed, and by making it 55% by weight or less, sufficient bonding strength can be ensured.

[0026] The photopolymerization initiator (D) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, benzyl ketals include 2,2-dimethoxy-1,2-diphenylethan-1-one, α-hydroxyacetophenones include 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, α-aminoacetophenones include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and acylphosphine oxides include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, which may be used alone or in combination of two or more.

[0027] Among the (D) above, it is preferable to use an α-hydroxyacetophenone type which is less prone to yellowing. Commercially available products include DAIDO UV-CIRE#174 (trade name: manufactured by Daido Chemical Industry Co., Ltd.).

[0028] The amount of (D) is preferably 5 to 15 parts by weight, more preferably 8 to 12 parts by weight, based on 100 parts by weight of the photopolymerizable component. By adding it within this range, the composition can be cured efficiently without excessive addition.

[0029] The composition of the present invention preferably further contains a reactive diluent (E). In particular, it is preferable that the diluent is a hydroxyl group-containing (meth)acrylate capable of dissolving the (A) component. For example, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 1,4-cyclohexanedimethanol monoacrylate, 4-hydroxycyclohexyl (meth)acrylate, etc. can be mentioned, and they can be used alone or in combination of two or more kinds. Among these, 4-hydroxybutyl acrylate (hereinafter referred to as 4HBA) is preferable because it has excellent solubility for (A).

[0030] The amount of the (E) to be blended is preferably 25% by weight or less, more preferably 20% by weight, and particularly preferably 15% by weight, based on the total solid content. If the amount is 25% by weight or less, the composition can be diluted without significantly affecting the peel strength or the increase rate of the peel strength.

[0031] The composition of the present invention may contain various additives such as leveling agents, tackifiers, antioxidant pigments, dyes, light stabilizers, defoamers, UV absorbers, and wettability adjusters, as necessary, within the range that does not impair the performance.

[0032] The viscosity of the composition at 25° C. is preferably 50 to 1,000 mPa·s, and more preferably 100 to 800 mPa·s. By making it 50 mPa·s or more, it becomes easier to ensure a sufficient coating amount, and by making it 1,000 mPa·s or less, it becomes possible to ensure sufficient coating smoothness.

[0033] When the composition is applied, the film thickness is preferably 2 to 50 μm, more preferably 3 to 40 μm, and particularly preferably 4 to 35 μm. By setting the film thickness within this range, the peeling force does not increase rapidly over time, and furthermore, removability can be maintained with a low peeling force. In addition, when inkjet printing is performed, the film thickness is set to 15 μm or more to sufficiently suppress the transfer of ink.

[0034] After the composition is applied to a substrate and cured, the peel strength (initial) immediately after pressure bonding and the peel strength after aging for one week at 23° C. after bonding are preferably 0.1 to 10 N / 6 inch, more preferably 0.3 to 5 N / 6 inch. If the strength is within this range, it can be said that sufficient removability is ensured without the ink transferring to the coating surface even when printing with an inkjet.

[0035] After applying this composition to a substrate and curing it, the increase in peel strength over time from the initial peel strength immediately after pressing and then curing at 23°C for one week after lamination is preferably 150% or less, and more preferably 110% or less.

[0036] The present invention will be described in more detail below with reference to examples and comparative examples, but these are illustrative and are not intended to be limiting. Unless otherwise specified, measurements were performed under conditions of room temperature of 25°C and relative humidity of 65%. The amounts of the ingredients are expressed in parts by weight. EXAMPLES

[0037] Examples and Comparative Examples In a light-shielding bottle, KURARITY LA2140 (trade name: manufactured by Kuraray Co., Ltd., PMMA-PnBA-PMMA triblock copolymer, Mw 77,000, MMA ratio 20%), KURARITY LA2330 (trade name: manufactured by Kuraray Co., Ltd., same triblock copolymer, Mw 122,000, MMA ratio 20%), and KURARITY LA2270 (trade name: Kuraray Co., Ltd., triblock copolymer, Mw70,000, MMA ratio 40%), (B) M2100 (trade name: Miwon Co., Ltd., EO modification number 10), (C) M300 (trade name: Miwon Co., Ltd., TMPTA) and M360 (trade name: Miwon Co., Ltd., propylene oxide adduct of TMPTA (3)), M4100 (trade name: Miwon Co., Ltd., DTMPT4A) and PET-30 (trade name: Nippon Kayaku Co., Ltd., mixture of PET3A and PET4A), (D) UV-CURE # 174 (trade name: Daido Kasei Co., Ltd., α-hydroxyacetophenone system), (E) 4-HBA (trade name: Osaka Organic Chemical Industry Co., Ltd.) were added in the amounts shown in Tables 1 and 2, and stirred until homogeneous using a stirring defoamer to prepare the pressure-bonded composition of the examples and comparative examples.

[0038] Preparation of evaluation sheet The adhesive composition was applied to New V Mat (product name: matte coated paper manufactured by Mitsubishi Paper Mills) using a bar coater #5 (film thickness 5 μm), and then exposed to UV light with an output of 90 mW / cm using an electrode UV irradiation device, Aimini Grandage ECS-151U manufactured by AiGraphics Co., Ltd. 2 , cumulative light intensity 80mJ / cm 2 The sheet was cured under the above conditions, folded in half with the coated surface on the inside, and the cured resin surfaces were placed together and pressed together using a postcard pressing machine, PRESSLE Bee, manufactured by Toppan Forms, to produce an evaluation sheet.

[0039] [Table 1]

[0040] [Table 2]

[0041] The evaluation method was as follows.

[0042] Viscosity: Measurements were taken using a Toki Sangyo cone-plate viscometer RC-550 with a cone angle of 3°R17.65 at 25±1°C and a rotation speed of 100 rpm for viscosity ranges of 500 mPa·s or less and 30 rpm for viscosity ranges of 500-1000 mPa·s.

[0043] Peel strength: The laminated sheet was cut to a width of 250 mm, and a T-shaped peel was performed at a peel speed of 300 mm / min using a Techno Graph tensile tester TGI-1kN. Measurements were taken immediately after compression and after one week of curing at 23°C, and five measurements were taken for each, with the average of three measurements excluding the maximum and minimum values ​​being taken. For both the initial and one week of curing, 0.1 to 5.0 N or more was indicated as ⊚, more than 5.0 N to less than 10 N was indicated as ◯, and 10 N or more was indicated as ×.

[0044] Peel strength increase rate: The ratio of peel strength after one week of curing to the initial value was marked as ◎ if it was 110% or less, ◯ if it was between 110% and 150%, and × if it was 150% or more.

[0045] Damage to the substrate: The state of the substrate after the peel test was visually inspected. If there was no damage, it was rated as ◯, and if there was damage, it was rated as ×.

[0046] Evaluation results The evaluation results are shown in Tables 3 and 4.

[0047] [Table 3]

[0048] [Table 4]

[0049] The resin compositions of the Examples were evaluated to be good in terms of viscosity, peel strength, rate of increase in peel strength, and substrate breakage.

[0050] On the other hand, Comparative Example 1, in which (C) was below the lower limit, had a high peel strength and caused material breakage, Comparative Example 2, in which (C) was above the upper limit, and Comparative Example 3, which did not contain (B), had too low adhesion to allow compression bonding, and Comparative Example 4, which did not contain (C), had too low compatibility, and none of these were suitable for the present invention.

Claims

1. A photocurable removable pressure-sensitive adhesive composition comprising an acrylic block copolymer (A), an ethylene oxide-modified bisphenol A diacrylate (B), a polyfunctional (meth)acrylate (C), and a photopolymerization initiator (D), wherein (C) is derived from trimethylolpropane and / or pentaerythritol, and the amount of (C) is 15 to 55% by weight based on the total solid content.

2. 2. The photocurable removable pressure-sensitive adhesive composition according to claim 1, wherein the (A) is a triblock copolymer elastomer of methyl methacrylate and butyl acrylate.

3. 2. The photocurable removable pressure-sensitive adhesive composition according to claim 1, further comprising a reactive diluent (E).

4. A pressure-sensitive adhesive paper having a cured layer of the photocurable removable pressure-sensitive adhesive composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • JP1975008934A

  • Active energy ray-curable crimping varnish composition

    JP2021075614A